Toward a multilateral framework for investment - Nicolle Graugnard (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Ahead of this year's G20 Summit, global business is recommending that the G20 agree upon a set of recommendations governing a G20 multilateral investment framework. From the perspective of the International Chamber of Commerce, this recommendation represents a long-term objective of establishing a comprehensive high-standard regime that businesses can rely upon to generate sustainable growth.
Keywords: 330